Anti-inflammatory effect of lycopene in SW480 human colorectal cancer cells - Cha, Jae Hoon; Kim, Woo Kyoung; Ha, Ae Wha; Kim, Myung Hwan; Chang, Moon Jeong (Nutrition research and practice, 2017)
Although the antioxidative effects of lycopene are generally known, the molecular mechanisms underlying the anti-inflammatory properties of lycopene are not fully elucidated. This study aimed to examine the role and mechanism of lycopene as an inhibitor of inflammation. Lipopolysaccharide (LPS)-stimulated SW 480 human colorectal cancer cells were treated with 0, 10, 20, and 30 µM lycopene. The MTT assay was performed to determine the effects of lycopene on cell proliferation. Western blotting was performed to observe the expression of inflammation-related proteins, including nuclear factor-kappa B (NF-κB), inhibitor kappa B (IκB), mitogen-activated protein kinase (MAPK), extracellular signal-related kinase (ERK), c-jun NH2-terminal kinase (JNK), and p38 (p38 MAP kinase). Real-time polymerase chain reaction was performed to investigate the mRNA expression of tumor necrosis factor α (TNF-α), interleukin-1 beta (IL-1β), interleukin-6 (IL-6), inducible nitric oxide synthase (iNOS), and cyclooxygenase-2 (COX-2). Concentrations of nitric oxide (NO) and prostaglandin E (PGE ) were determined via enzyme-linked immunosorbent assays. In cells treated with lycopene and LPS, the mRNA expression of TNF-α, IL-1β, IL-6, iNOS, and COX-2 were decreased significantly in a dose-dependent manner ( < 0.05). The concentrations of PGE and NO decreased according to the lycopene concentration ( < 0.05). The protein expressions of NF-κB and JNK were decreased significantly according to lycopene concertation ( < 0.05). Lycopene restrains NF-κB and JNK activation, which causes inflammation, and suppresses the expression of TNF-α, IL-1β, IL-6, COX-2, and iNOS in SW480 human colorectal cancer cells.